[Behind rebel lines ; Tullahan River ; Aizamania] - Lazaro, Cheche (The Probe Team, 1988)
Features the ceasefire between NPA rebels and the military with the interview of TPT with the insurgents ; a polluted river and its damage to environment and interview with Aiza Seguerra.